Earthworm-induced shifts in microbial diversity in soils with rare versus established invasive earthworm populations. Issue 5 (22nd March 2018) - de Menezes, Alexandre B; Prendergast-Miller, Miranda T; Macdonald, Lynne M; Toscas, Peter; Baker, Geoff; Farrell, Mark; Wark, Tim; Richardson, Alan E; Thrall, Peter H
Abstract: European earthworms have colonised many parts of Australia, although their impact on soil microbial communities remains largely uncharacterised. An experiment was conducted to contrast the responses to Aporrectodea trapezoides introduction between soils from sites with established (Talmo, 64 A. trapezoides m −2 ) and rare (Glenrock, 0.6 A. trapezoides m −2 ) A. trapezoides populations. Our hypothesis was that earthworm introduction would lead to similar changes in bacterial communities in both soils. The effects of earthworm introduction (earthworm activity and cadaver decomposition) did not lead to a convergence of bacterial community composition between the two soils. However, in both soils, the Firmicutes decreased in abundance and a common set of bacteria responded positively to earthworms. The increase in the abundance of Flavobacterium, Chitinophagaceae, Rhodocyclaceae and Sphingobacteriales were consistent with previous studies. Evidence for possible soil resistance to earthworms was observed, with lower earthworm survival in Glenrock microcosms coinciding with A. trapezoides rarity in this site, lower soil organic matter and clay content and differences in the diversity and abundance of potential earthworm mutualist bacteria. These results suggest that while the impacts of earthworms vary between different soils, the consistent response of some bacteria may aid in predicting the impacts of earthworms on soil ecosystems. Abstract : Re-introduction of invasive earthworms into soils from sites where they were rare or established reveals subtle but consistent effects on the soil microbiome and evidence for soil resistance to earthworms.